Video quality measurement standards - Current status and trends - Winkler, S. (2009 7th International Conference on Information, Communications and Signal Processing, 2009)
With the wide-spread use of digital video, quality considerations have become essential, and industry demand for video quality measurement standards is rising. Various organizations are working on such standards. This paper reviews some of the existing standards documents, on-going work and future trends in this space.